2006
DOI: 10.4319/lo.2006.51.6.2586
|View full text |Cite
|
Sign up to set email alerts
|

Unsynchronised and synchronised vertical migration of zooplankton in a high Arctic fjord

Abstract: We measured vertical migration of zooplankton in an arctic fjord at 79uN between June and September 2002 and transcending a period of continuous illumination to one of true day and night to investigate the changing influence of light cues on behavior. Observations made with a moored 300 kHz acoustic Doppler current profiler indicated that two modes of vertical migration occurred during the study period. During the weeks of continuous illumination, backscatter data indicated that there was no net vertical displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 41 publications
(79 reference statements)
5
101
0
1
Order By: Relevance
“…al., 2001;BlachowiakSamolyk et. al., 2006;Cottier et al, 2006;Falk-Petersen et al, 2008;Berge et al, 2009;Benoit et al, 2010;Rabindranath et al, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…al., 2001;BlachowiakSamolyk et. al., 2006;Cottier et al, 2006;Falk-Petersen et al, 2008;Berge et al, 2009;Benoit et al, 2010;Rabindranath et al, 2010).…”
Section: Introductionunclassified
“…Although zooplankton populations do not migrate vertically in a synchronised manner during midnight sun conditions, Cottier et al (2006) and Wallace et al (2010) found evidence that individuals within those populations performed forays in and out of the surface layers throughout the 24-h cycle. While their backscatter data indicated that there was no net vertical displacement of the population at any time during the 24-h period, the vertical velocity showed a continuous net downward movement in the surface layers and a net upward movement at depth, which represents the so-called unsynchronised DVM.…”
Section: Cottier Et Al (2006) Measured the Dvm Of Zooplankton In An mentioning
confidence: 99%
“…Thus the observed non-existence of local functional response is presumably a consequence of complex foraging behaviour of zooplankton at intermediate time and space scales and not a result of noise. Note that this phenomenon is rather different from the dailybased vertical migration pattern since it implies an exchange of organisms between different layers in a unsynchronized way without a pronounced alteration of the vertical profile of zooplankton (Leising et al, 2005;Cottier et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Feeding of zooplankton in the ocean (or deep lakes) implies existence of complex foraging cycles characterized by permanent exchange of grazers between surface and deep layers (Pearre, 1979;Leising et al, 2005, Cottier et al, 2006. In this paper, we provide an example of such unsynchronized vertical migration for herbivorous copepods based on our field data.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation